2013
DOI: 10.1016/j.neuroscience.2013.01.015
|View full text |Cite
|
Sign up to set email alerts
|

The role of the serotonergic system at the interface of aggression and suicide

Abstract: Alterations in serotonin (5-HT) neurochemistry have been implicated in the aetiology of all major neuropsychiatric disorders, ranging from schizophrenia to mood and anxiety-spectrum disorders. This review will focus on the mulifaceted implications of 5-HT-ergic dysfunctions in the pathophysiology of aggressive and suicidal behaviours. After a brief overview of the anatomical distribution of the 5-HT-ergic system in the key brain areas that govern aggression and suicidal behaviours, the implication of 5-HT mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 388 publications
(469 reference statements)
1
73
0
4
Order By: Relevance
“…Alterations in serotonin (5-Ht) neurochemistry have been implicated in the aetiology of all major cerebral disorders, ranging from schizophrenia to mood and anxiety-spectrum disorders including epilepsy (Di Giovanni et al 2008;Bombardi and Di Giovanni 2013;Bortolato et al 2013). Moreover, a dysfunctional serotonergic system might be responsible for the occurrence of concomitant diseases such as temporal lobe epilepsy (tLE) and comorbid depression and cognitive impairments and depression (Kanner and Balabanov 2002;Garcia 2012;theodore et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in serotonin (5-Ht) neurochemistry have been implicated in the aetiology of all major cerebral disorders, ranging from schizophrenia to mood and anxiety-spectrum disorders including epilepsy (Di Giovanni et al 2008;Bombardi and Di Giovanni 2013;Bortolato et al 2013). Moreover, a dysfunctional serotonergic system might be responsible for the occurrence of concomitant diseases such as temporal lobe epilepsy (tLE) and comorbid depression and cognitive impairments and depression (Kanner and Balabanov 2002;Garcia 2012;theodore et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to 5-Ht receptor dysfunction in suicide and aggression, the most studied have been the 5-Ht 1 , 5-Ht 2 subtypes (Bortolato et al 2013;Panariello et al 2011). We will focus on 5-Ht 2 receptors that have been implicated in a wide variety of conditions including obesity, anxiety, depression, obsessive compulsive disorder, schizophrenia, migraine and erectile dysfunction (Di Giovanni et al 2008.…”
Section: -Ht Receptor In Suicidal Behaviourmentioning
confidence: 99%
“…this is a process in which specific adenosine residues are converted to inosine resulting in functional recoding of the mRnA that can generate up to 24 different protein isoforms with distinct functional properties. Post-mortem, animal and pharmacological studies have suggested that 5-Ht2C receptor and their altered RnA editing is involved in the pathophysiology of mental disorders including aggression and suicide, although results remain inconsistent (Panariello et al 2011;Bortolato et al 2013;Di Giovanni et al 2006. For instance, an increased density of prefrontal cortex 5-Ht 2C R mRnA (Pandey et al 2006) and differences in pre-mRnA editing of these receptors between control subjects and suicidal victims have been found (Gurevich et al 2002;Dracheva et al 2008).…”
Section: -Ht 2c Receptors In Aggression and Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…Strong neurobiological evidence points toward serotonergic and noradrenergic dysfunction [35][36][37]. Dysregulation in serotonin (5-HT) neurotransmission also appears to be related to impulsiveaggressive behavior [38], which influences suicidal behavior as an intermediate phenotype [39].…”
Section: Introductionmentioning
confidence: 99%